Mac OS X power tools - Frakes, Dan (Sybex, 2004)
The book that Macintosh industry experts rave about, Mac OS X Power Tools, has been completely updated for version 10.3, Panther. If you want to go beyond the basics, this unique book provides extensive background information on the hows and whys of the OS, and then shows you how to get the most out of it through specific examples. Author Dan Frakes walks you through step-by-step instructions on how to customize, optimize, and maintain your Mac OS X system--better, faster, and more simply. Topic coverage includes customization, networking, security, file sharing, Unix, the latest features, extending OS X with third-party software, and much more.